2021
DOI: 10.1101/2021.04.17.21255540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thromboembolism risk among patients with diabetes/stress hyperglycemia and COVID-19

Abstract: Purpose. Individuals with diabetes carry an increased risk for adverse clinical outcome in case of SARS-CoV-2 infection. The purpose of this study was to evaluate whether this risk is, at least in part, modulated by an increase of thromboembolic complications. Methods. We prospectively followed 169 hospitalized patients with confirmed COVID-19 pneumonia admitted to the Internal Medicine Units of San Raffaele Hospital. We analysed inflammation and tissue damage biomarkers, hemostatic parameters, thrombotic eve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…However, several studies have reported that stress hyperglycemia Fig. 2 Restricted cubic splines for the odds ratio of in-hospital mortality is strongly associated with adverse clinical outcomes among patients with critical illnesses, including myocardial infarction, stroke, sepsis, and COVID-19 [11,18,19]. Stress hyperglycemia has been identified as an independent risk factor for worsened prognoses in patients with ACS [4][5][6]20].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported that stress hyperglycemia Fig. 2 Restricted cubic splines for the odds ratio of in-hospital mortality is strongly associated with adverse clinical outcomes among patients with critical illnesses, including myocardial infarction, stroke, sepsis, and COVID-19 [11,18,19]. Stress hyperglycemia has been identified as an independent risk factor for worsened prognoses in patients with ACS [4][5][6]20].…”
Section: Discussionmentioning
confidence: 99%
“…In our best knowledge, this is the first study specifically examining the impact of T2D on ROTEM®-tested coagulation in patients with mild COVID-19 pneumonia. On contrary, Calvisi et al previously in a prospective analysis of 180 hospitalized patients with COVID-19 pneumonia [17] reported that diabetes/stress hyperglycemia was associated with higher risk of thromboembolism (arterial and venous). In this study, patients with diabetes/stress hyperglycemia had increased inflammation, higher D-dimer levels, and lower antithrombin III activity.…”
Section: Discussionmentioning
confidence: 95%
“…[18] All these diabetes-related abnormalities might aggravate the risk of thrombosis and explain higher incidence of thrombotic events observed among COVID-19 patients with diabetes/stress hyperglycemia by Calvisi et al Another possible explanation is that stress hyperglycemia could act as a marker, rather than as a direct contributor of an increased risk of COVID-19-related thrombosis. Calvisi et al [17] reported an increased inflammation and tissue damage circulatory markers in those with diabetes/stress hyperglycemia. In our study, no significant differences were found in inflammatory markers between T2D and nondiabetic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 A study of hyperglycaemia (not specifically with HHS) during COVID-19 admissions suggested that the risk of arterial and VTE was three times higher than those without hyperglycaemia. 41 Other work has estimated that people with diabetes and hyperosmolality have a risk of VTE similar, or only marginally above those with acute renal failure, acute sepsis or acute connective tissue disease. 42,43 The risk of venous thromboembolism is greater than in diabetic ketoacidosis.…”
Section: Anticoagulationmentioning
confidence: 99%